Eigendecomposition filtering and reconstruction of the climatic indexes for the Brazilian Northeast - Corrêa, Cleber Souza; Guedes, Roberto Lage; Corrêa, Karlmer Abel Bueno (Ciência e Natura, 2018)
This work seeks through the intermediary of the eigendecomposition filtering and reconstructing technique the signal of the time series of Southern Oscillation Index (SOI), and analyze possible cycles that can be observed in this SOI time series. The technique of decomposition was very consistent and can show possible trends in cycles in time series of SOI. The final result is featuring a composition of components operating in the formation of the SOI variability signal, the first component is featuring approximately 1.33, 2.66, 3.58, 4.83 years and decadal time period, larger scales and periods, matching a variance approximately of 70% of the signal of the SOI time series. In addition to the influence of cycles of solar activity, associated with its number of sunspots, the variability observed from 20 to 27 years may be related to the interaction between Pacific Decadal Oscillation (PDO) and Southern Oscillation Index (SOI). The understanding the dynamics that control the decadal variability in the Pacific Ocean and its interactions with climate change on a global scale. These results can be correlated to behavior characteristics of the atmospheric dynamics and predominance in northeastern Brazil, has importance and affecting activities in Rocket Launch Centre in Alcântara (CLA).